2015
DOI: 10.3233/jad-140636
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Complaint Only Relates to Verbal Episodic Memory Performance in Mild Cognitive Impairment

Abstract: Background A cognitive concern from the patient, informant, or clinician is required for the diagnosis of mild cognitive impairment (MCI); however, the cognitive and neuroanatomical correlates of complaint are poorly understood. Objective We assessed how self-complaint relates to cognitive and neuroimaging measures in older adults with MCI. Method MCI participants were drawn from the Alzheimer’s Disease Neuroimaging Initiative and dichotomized into two groups based on the presence of self-reported memory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 66 publications
4
13
0
1
Order By: Relevance
“…27 SCCs are related most closely to episodic memory in patients with MCI. 28 We also found that some types of decline were more closely related to SCC than others. For example, the CVLT was related to SCC, whereas the memory/language cluster composed of other memory tests and tests of category fluency and naming was not related.…”
Section: Discussionsupporting
confidence: 53%
“…27 SCCs are related most closely to episodic memory in patients with MCI. 28 We also found that some types of decline were more closely related to SCC than others. For example, the CVLT was related to SCC, whereas the memory/language cluster composed of other memory tests and tests of category fluency and naming was not related.…”
Section: Discussionsupporting
confidence: 53%
“…Despite converging evidence, not all existing literature supports the potential validity of the items selected here. For example, the question “Do you feel that you have more memory problems than most?” (item 13 of the current bank) was not one of the SCD items selected by our advanced psychometric modeling techniques despite existing evidence that this question may be related to poorer episodic memory in MCI [45] . The discrepancy in current versus past work suggests that although this question is valid and one possibility for measuring SCD, the item may not be the most reliable method for assessing SCD.…”
Section: Discussionmentioning
confidence: 99%
“…SMCs were shown to correlate with informants' memory rating in adults diagnosed with Mild Cognitive Impairment (MCI) or dementia (Abner, Kryscio, Caban-Holt, & Schmitt, 2015; Buckley et al, 2015; Salem, Vogel, Ebstrup, Linneberg, & Waldemar, 2015), and to correlate with subjective mood (Yates, Clare, Woods, & Matthews, 2015). SMCs have also been associated with poorer verbal episodic memory performance (Gifford et al, 2015). However, previous studies in HIV have found stronger association between SMCs and mood (Au et al, 2008; van Gorp et al, 1991) rather than with cognitive performance.…”
Section: Introductionmentioning
confidence: 99%